DEVELOPMENT OF SMALL MEDIUM INDUSTRY SECTOR OF CUSTOMS IN KLUNGKUNG REGENCY - Purnamawati, I Gusti Ayu (Universitas Pendidikan Ganesha, 2017)
The main objectives of this research are: development of small and medium industries of wayang kamasan in Klungkung Regency in terms of: 1. Field of production; 2. Field Management; 3. Field of Cooperation and Licensing. Research methods used in the achievement of these objectives in the form of qualitative methods and data collection through interviews, observation and literature study. The results showed that: (1) Socialization of insight in the field of production, management, cooperation, and permission made by Disperindag Klungkung Regency get positive response from craftsmen; (2) In the selection of raw materials, the preparation of the list of products, finishing, design and packaging, including the preparation of the contract of sale and purchase agreement has been started by the craftsmen. (3) The high participation level of the community has a positive impact on the research implementation, as seen from the training and production and entrepreneurship training, cooperation and management of UBK licensing can run well.